Kemampuan Berpikir Kritis Peserta Didik pada Pembelajaran Kimia dalam Pokok Bahasan Laju Reaksi di SMA Negeri 1 Bantarbolang - Retno Setianingsih; Mega Novita; Siti Patonah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
This study aims to describe students' critical thinking skills in the subject of reaction rates. The research subjects were 180 class XI students and 36 students were taken as samples at SMA Negeri 1 Bantarbolang. In this study using qualitative methods, data were collected using 10 critical thinking skills test questions that represent 4 aspects of critical thinking, including aspects of providing explanations, building basic skills, managing strategies and tactics, and concluding. Students who have been taught this material to spell according to their abilities. Through the google form that has been sent students work on these questions. The results show that the overall thinking ability of students is 36.87 including the low category.